RATING RESOURCES CONSUMPTION AT LOCAL SCALE FOR GETTING SUSTAINABILITY (PANGEEA, 2025)
ABSTRACT: Our human life has always been based on more or less resources consumption, being actually a sine-qua-non condition for carrying out different human activities. With the goal of assuring sustainability of our human society there is a need to assess economic activities, especially industrial processes not only from economic and technical points of view but from environmental and social ones as well. Human economic activities, especially industrial ones have the set aim to facilitate maintaining and if possible the growth of the quality of life of humanity. However these can have beside desired positive impacts also undesired negative and sometimes unthinkable ones on environment and society. Many tryings have underlined that for successful sustainability operationalisation there is a need to consider different scales, global, national, regional as well as local scale. Regarding getting sustainability at a local scale there is a need to make the connection to urban resources consumption, not at least in the effort of finding future options for renewable resources, based on water, wind, and solar energy to be applied in urban areas. Existing odds to assure adequate urban resources consumption for getting sustainability at local scale will be emphasized by taking into consideration minimal unwanted environmental and social impacts. Connected to this idea, developing a kind of a general methodology to be applied for real concrete situations by considering regional differences would represent a major advance in this field.
Keywords: rating resources consumption; sustainability; local scale; consumption patterns; environmental impact